Secagem de pimenta-do-reino preta (Piper nigrum L.) em secador de leito fixo - Alves, Danilo Aparecido Serafim (2015)
The black pepper is the most important spice commercialized globally, with Brazil being one of the main producers in the world. Yet few studies to optimize the production of this commodity process have been found in the literature. The objective of this work was to study the drying the black pepper grains. The physicochemical characterization of the material with varying humidity, measuring linear dimensions (mean Sauter diameter, minimum, average and maximum diameter, and perimeter) was performed, as well as surface area, volume, sphericity, and also the bulk density, real and bulk, porosity and grain. Drying experiments were conducted in a hothouse at different temperatures. Assays were carried out a fixed-bed dryer for determination of the thin layer. Drying kinetics experiments were performed on a thin layer in a dryer with forced convection temperature ranging from 50 to 70 °C, and air velocity of 1.0, 2.0 and 4.0 m/s. With these data, there have been adjustments of Lewis, Page and Overhults equations, and the Forward model with simplifying assumptions for the diffusivity. The results obtained show that the diffusive model was the most suitable. It also promoted the essential oil extraction of the grains and the results are consistent with the literature.